Fingerprinting of anti-citrullinated protein antibodies (ACPA): specificity, isotypes and subclasses. (April 2015) - Pratesi, F; Panza, F; Paolini, I; Petrelli, F; Puxeddu, I; Casigliani-Rabl, S; Ancillotti, D; Alcaro, C; Rovero, P; Migliorini, P
Anti-citrullinated protein antibodies (ACPA) are a family of rheumatoid arthritis (RA)-specific autoantibodies that recognize the amino acid citrulline, resulting from the post-translational modification of arginine. Peptidyl arginine deiminase, the enzyme responsible for citrullination, is present in humans in different isoforms with different tissue distribution, enzymatic activity and target specificity; nonetheless, the number of proteins citrullinated in physiological or pathological conditions is wide, but not every citrullinated protein is a target for antibodies. In pre-RA patients the immune response to citrullinated antigens is initially restricted, expands with time and, after the onset of the disease, is relatively stable. ACPA are heterogeneous in terms of not only fine specificity but also isotype and IgG subclasses usage. This heterogeneity may be relevant for the immunopathogenesis of RA, conditioning the interaction of antibodies with complement and Fc receptors.